Developing a conceptual framework for interdisciplinary communication, collaboration, and integration: A structured approach - Jialin Zhang; Hanna Salomon; Martin Nicola Huber; Harald Bugmann; Julie Elisabet Dölker; Louis König; Jasmin Krähenbühl; Eva Lieberherr; Ivana Logar; Brian McArdell; Peter Molnar; Simone Quatrini; et al. (Ambio, 2025)
Interdisciplinary research is essential to address the complex environmental challenges faced by social-ecological systems (SES). However, it is often hindered by difficulties in integrating diverse knowledge and perspectives. Conceptual Frameworks (CFs) can act as boundary objects, facilitating integration in contexts with incomplete knowledge, nonlinearity, and divergent interests. Yet, guidance on developing CFs remains limited. To address this gap, we develop a structured approach and apply it within a research project focused on enhancing the resilience of Swiss Alpine ecosystems. Our approach includes three phases: (1) defining boundary concepts, (2) developing a CF as a boundary object, and (3) using the CF as a boundary object. The resulting CF supports communication, collaboration, and integration across disciplines, advancing SES research that addresses ecological resilience and sustainability. Our approach can be used by other interdisciplinary teams aiming to develop adaptable CFs that facilitate knowledge integration across disciplines.